Philosophical Hermeneutics: A Path to Intercultural Understanding Through Translation - Panahbar, Ehsan; Dabaghi, Azizollah (Mediterranean Journal of Social Sciences, 2012)
In philosophical hermeneutics, the thoughts of Gadamer and Ricoeur about conditions of attaining to understandingare of utmost interest. Gadamer, by proposing "fusion of horizons" and considering the prejudices of interpreter as basic factorsof interpreting and understanding of all phenomena, and Ricoeur, by believing that we as human being only can understand theSelf through understanding Other, have paved the paths to attaining intercultural understanding. This study tried to investigatethe fundamental role of translation in the intercultural understanding from the window of philosophical hermeneutics, becauseaccording to Gadamer all understandings occur in language and this asserts that translation, as a linguistic and culturalphenomenon, can, after catastrophe of Babel, take the hearts and tongues of scattered human beings close to each other andas Ricoeur believes, humanity enjoys equivalence in spite of alterity.